FUNGSI KEPEMIMPINAN KEPALA DESA DALAM PENINGKATAN KINERJA APARATUR DESA SIDERA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Borahima, Muhammad Husain (Katalogis, 2020)
This reseach aims at finding out the role of village head in improving the performance of Village Apparatus in Sidera Village, Sigi Biromaru Sub-District, Sigi Regency. The problem in the village office was the competence of the village apparatus in doing the job related to government adminitration and strengthen the society’s participation was still not effective. Therefor, the leadership of village head plays an important role in realizing the good performance of the apparatus in giving good service to the society. This is qualitative descriptive research using prequency table and percentage. The research population were 26 apparatus at Sidera village office, Sigi Biromaru sub-district. The sample was taken through saturated sample or set all the population as samples. The data were collected through observationm, interview, questionnaire, and documentation. The results show that the role of leadership of head village on the improvement of village apparatus’ performance at Sidera village office, Sigi Biromaru sub-district, in relation to the productivity indicator, service quality, and responsiveness are still not effective. It is caused by the inability of village apparatus to give nice response toward the complain and the needs of the society. Furthermore, related to then leadership function of the head village, such as taking decision, instructive function, consultative function, and participative function are very well.